International management : managing across borders and cultures : text and cases - Deresky, Helen (New York : Pearson, 2023)
"International Management: Managing Across Borders and Cultures explores how recent developments and trends within a hypercompetitive digitally driven global economy present managers with challenging situations. Companies seeking to operate overseas are confronted with varied and dynamic environments in which they must accurately navigate the political, legal, technological, competitive, and cultural factors that shape their strategies and operations. The fate of overseas operations depends greatly on the international manager's cultural skills and sensitivity as well as on their ability to carry out the company's strategy within the context of the host country's business practices"--
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: International business enterprises -- Management; International business enterprises -- Management -- Case studies; Industrial management